Managing IaaS and DBaaS clouds with Oracle enterprise manager cloud control 12c : implement comprehensive cloud computing solutions efficiently using Oracle enterprise manager /: implement comprehensive cloud computing solutions efficiently using Oracle enterprise manager. (2013) - Unknown
No abstract available